The Urgency of Regulation in the Case of Online Gender-Based Violence in Indonesia - Genie Cyprien; Muhammad Iqbal (Sawwa: Jurnal Studi Gender, 2021)
The National Commission for Women 2020 Annual Notes reminded a new type of violence against gender, namely cyber-based or online gender violence, which continued to increase over the past six years, with an increase of 300% in Online Gender-Based Violence (OGBV) compared to 2019. The OGBV case was found on various popular social media platforms. The most common incidents occurred on Facebook, where 39% of women experienced harassment. This figure is then followed by Instagram (23%), Whatsapp (14%), Snapchat (10%), Twitter (9%), and TikTok (6%). The study aimed at examining factors influencing online gender-based violence. It was a survey, which used questionnaires as the method of collecting data. The data were collected from 109 respondents. The study shows that online gender-based violence is influenced by two factors, namely regulatory factors that are still unable to protect women in social media and social factors that have been cultured. There is a perspective that views women as having a weaker position than men. These two factors are the most significant in promoting online gender-based violence in Indonesia. The results suggest the urgency of regulations dealing with the protection of women against violence in online media.